Exploring Sex Differences in Risk Factors and Quality of Life Among Tuberculosis Patients in Herat, Afghanistan: A Case-Control Study - Nasar Ahmad Shayan; Nasar Ahmad Shayan; Ali Rahimi; Ali Rahimi; Saverio Stranges; Saverio Stranges; Saverio Stranges; Saverio Stranges; Amardeep Thind; Amardeep Thind (Frontiers Media S.A., 2024)
Objectives: Tuberculosis (TB) is a significant public health concern in Afghanistan, with a high burden of disease in the western province of Herat. This study explored the risk factors of TB and TB's impact on the quality of life of patients in Herat.Methods: A total of 422 TB patients and 514 controls were recruited at Herat Regional Hospital and relevant TB laboratories between October 2020 and February 2021. Data was collected through interviews using a structured questionnaire and the SF-36 questionnaire. Descriptive statistics, chi-square tests, Multivariate General Linear Model, and logistic regression analysis were used to analyze the data.Results: The results showed that male sex (p = 0.023), chronic disease (p = 0.038), lower education levels (p < 0.001), and worse health status (p < 0.001) were significantly associated with higher odds of TB infection. The study also found that TB patients had significantly lower quality of life scores in almost all components (p < 0.05).Conclusion: This study provides important insights into the specific ways in which TB affects the wellbeing of patients in Afghanistan. The findings highlight the importance of addressing the psychological and social dimensions of TB.